Elements for a postcolonial pedagogy in Cedric Robinson's Black Marxism - Gabriele Borghese (University of Bologna, 2023)
The essay focuses on the pedagogical elements present in Cedric Robinson's Black Marxism on the genesis of the African American radical tradition. Robinson's intent is to criticize the categories of classical Marxism, showing how racialization is an intrinsic element of the economic structure of Western societies, further deepening the category of racial capitalism and going so far as to deny some of the liberatory and progressive features of the rise of capitalism and the bourgeois class. He profoundly relates the development of capitalism from its origin with colonial missions that were aimed to develop education in colonial territories. When Robinson analyzes the function that education played in the formation of the early black intelligentsia the pedagogical importance of his analysis emerges. The colonial education system prepared the ground for the formation of a black middle class that in Africa and India served as an intermediary between enslaved workers and colonialists. Members of the native middle class showed complicity with the colonial state, yet at the same time experienced the condition of oppressed and oppressor. This contradiction gave rise to the formation of the first black radical intelligentsia during World War I.